2020
DOI: 10.21203/rs.3.rs-51260/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Microalgae Aurantiochytrium Sp. Increases Neurogenesis and Improves Spatial Learning and Memory in Senescence-Accelerated Prone 8 Mice

Abstract: Background Much attention has recently focused on nutraceuticals which are widely used to promote health. In particular, nutraceuticals with minimal side effects have been developed for preventing or treating neurological diseases such as Alzheimer’s disease (AD). The present study was conducted to investigate the potential effect on neural development and function of the microalgae Aurantiochytrium sp. as a nutraceutical. Methods To test the neuroprotection of ethanol extract of Aurantiochytrium (EEA) and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…In hAESCs, isorhamnetin showed anti-fibrotic potential, which was then validated in the cardiac fibrosis in vivo model (Aonuma et al, 2020). The observed neuroprotective potential of microalgaederived squalene (Ferdousi et al, 2021) has also been validated in aging model mice (Sasaki et al, 2019b;Sasaki et al, 2020). Similarly, the chemical synaptic transmission activity of RA was observed in depression model mice (Sasaki et al, 2013;Kondo et al, 2015), and the neurogenesis-regulating effect of TCQA was confirmed in aging mice (Sasaki et al, 2019a).…”
Section: Haescs As a Drug Screening Tool For Natural Compoundsmentioning
confidence: 81%
“…In hAESCs, isorhamnetin showed anti-fibrotic potential, which was then validated in the cardiac fibrosis in vivo model (Aonuma et al, 2020). The observed neuroprotective potential of microalgaederived squalene (Ferdousi et al, 2021) has also been validated in aging model mice (Sasaki et al, 2019b;Sasaki et al, 2020). Similarly, the chemical synaptic transmission activity of RA was observed in depression model mice (Sasaki et al, 2013;Kondo et al, 2015), and the neurogenesis-regulating effect of TCQA was confirmed in aging mice (Sasaki et al, 2019a).…”
Section: Haescs As a Drug Screening Tool For Natural Compoundsmentioning
confidence: 81%